Extraordinary strength-ductility synergy in a heterogeneous-structured β -Ti alloy through microstructural optimization. Issue 11 (2nd November 2019) - Shin, Sumin; Zhu, Chaoyi; Zhang, Cheng; Vecchio, Kenneth S.
ABSTRACT: This paper reports on a heterogeneous-structured β-Ti alloy with an exceptional combination of high strength and ductility, resulting from optimized hierarchical features in a lamellar microstructure. The microstructure is achieved by controlling a fraction of coarse/fine domains, spatial grain-size distribution, and different types of grain boundaries. The large degree of microstructural heterogeneity leads to obvious mechanical incompatibility and strain partitioning during plastic deformation. In addition, experimental results demonstrate that the unique heterogeneous structure induces high hetero-deformation induced hardening and promotes dislocation accumulation, thereby achieving a high yield strength ∼970 MPa and uniform tensile elongation of ∼16%. GRAPHICAL ABSTRACT: IMPACT STATEMENT: Microstructural heterogeneities can induce inhomogeneous deformation behavior, which leads to steep strain gradients, and consequently the potential to achieve enhanced strength-ductility synergy.